Ovarian follicles are resistant to monocyte perturbations—implications for ovarian health with immune disruption. Issue 1 (11th March 2021) - Sominsky, Luba; Younesi, Simin; De Luca, Simone N; Loone, Sophie M; Quinn, Kylie M; Spencer, Sarah J
Abstract: Monocytes and macrophages are the most abundant immune cell populations in the adult ovary, with well-known roles in ovulation and corpus luteum formation and regression. They are activated and proliferate in response to immune challenge and are suppressed by anti-inflammatory treatments. It is also likely they have a functional role in the healthy ovary in supporting the maturing follicle from the primordial through to the later stages; however, this role has been unexplored until now. Here, we utilized a Cx3cr1-Dtr transgenic Wistar rat model that allows a conditional depletion of circulating monocytes, to investigate their role in ovarian follicle health. Our findings show that circulating monocyte depletion leads to a significant depletion of ovarian monocytes and monocyte-derived macrophages. Depletion of monocytes was associated with a transient reduction in circulating anti-Müllerian hormone (AMH) at 5 days postdepletion. However, the 50–60% ovarian monocyte/macrophage depletion had no effect on ovarian follicle numbers, follicle atresia, or apoptosis, within 5–21 days postdepletion. These data reveal that the healthy adult ovary is remarkably resistant to perturbations of circulating and ovarian monocytes despite acute changes in AMH. These data suggest that short-term anti-inflammatory therapies that transiently impact on circulating monocytes are unlikely to disrupt ovarian follicle health, findings that have significant implications for fertility planning relative to the experience of an immune challenge or immunosuppression. Abstract : Summary sentence: Here we report that ovarian follicles are uniquely resilient against transient immune imbalance and are fully able to withstand the acute depletion of circulating and ovarian monocytes.